Accelerated vascular aging: Ethnic differences in basilar artery length and diameter, and its association with cardiovascular risk factors and cerebral small vessel disease - Sudre, Carole H.; Moriconi, Stefano; Rehwald, Rafael; Smith, Lorna; Tillin, Therese; Barnes, Josephine; Atkinson, David; Ourselin, Sébastien; Chaturvedi, Nish; Hughes, Alun D.; Jäger, H. Rolf; Cardoso, M. Jorge (Frontiers in Cardiovascular Medicine, 2022)
Background and aims: Risk of stroke and dementia is markedly higher in people of South Asian and African Caribbean descent than white Europeans in the UK. This is unexplained by cardiovascular risk factors (CVRF). We hypothesised this might indicate accelerated early vascular ageing (EVA) and that EVA might account for stronger associations between cerebral large artery characteristics and markers of small vessel disease. Methods: 360 participants in a tri-ethnic population-based study (120 per ethnic group) underwent cerebral and vertebral MRI. Length and median diameter of the basilar artery (BA) were derived from Time of Flight images, while white matter hyperintensities (WMH) volumes were obtained from T1 and FLAIR images. Associations between BA characteristics and CVRF were assessed using multivariable linear regression. Partial correlation coefficients between WMH load and BA characteristics were calculated after adjustment for CVRF and other potential confounders. Results: BA diameter was strongly associated with age in South Asians (+11.3μm/year 95% CI=[3.05;19.62]; p=0.008), with unconvincing relationships in African Caribbeans (3.4μm/year [ 5.26,12.12]; p=0.436) or Europeans (2.6μm/year [-5.75,10.87]; p=0.543). BA length was associated with age in South Asians (+0.34mm/year [0.02;0.65];p=0.037) and African Caribbeans (+0.39mm/year [0.12 ; 0.65]; p=0.005) but not Europeans (+0.08 mm/year [-0.26; 0.41];p=0.653). BA diameter (rho=0.210;p=0.022) and length (rho=0.261;p=0.004) were associated with frontal WMH load in South Asians (persisting after multivariable adjustment for CVRF). Conclusions Compared with Europeans, the basilar artery undergoes more accelerated EVA in South Asians and in African Caribbeans, albeit to a lesser extent. Such EVA may contribute to the higher burden of CSVD observed in South Asians and excess risk of stroke, vascular cognitive impairment and dementia observed in these ethnic groups.